What Keeps Visitors Coming Back? Factors Shaping Revisit Intention - Kevin Richardo Tanoto; Margaretha Pink Berlianto (Yayasan Riset dan Pengembangan Intelektual, 2025)
Healthy individuals have a greater capacity to work productively and creatively, which will impact the quality of human resources. This study examines factors that can influence revisit intention, exercise adherence, and word of mouth among members of a clubhouse in Tangerang. The study was conducted quantitatively on 227 respondents who are members of KYZN Clubhouse using a purposive sampling technique. The results show that service quality, service convenience, and exercise satisfaction are factors that can influence word of mouth intention, as well as service quality and exercise satisfaction that can influence revisit intention, and service convenience and exercise satisfaction can influence exercise adherence. It is recommended that companies can pay attention to these three aspects, especially service quality, because it is the most important factor in influencing members' revisit intention.